الصيغ الخلافية في المذهب الشافعي: دراسة وصفية تحليلية: Contentious Languages in Shafi Jurisprudence School of Thought: Descriptive and Analytical Study - El-Husseini Sayed Ahmed Zayed, Ali Zenelabidin (Al-Basirah Journal, 2021)
This research, Contentious Languages in Shafi Jurisprudence School of Thought: Descriptive and Analytical Study, deals with a key issue related to controversial terminologies in shafi jurisprudence school of thought. It draws its content material from books pertaining to Shafi School of Thought. Hence, the research at hand, aims to explain these terminologies and its impact on jurisprudential controversy. The research uses inductive method in deducing some examples that can serve as explanatory tools to these contentious languages. Likewise, it uses analytical method to assess issues on the usage of these contentious languages. Finally, the research uses descriptive method in displaying the subject-matter by highlighting the jurisprudential controversy and its contentious languages.